Understanding Eco-anxiety: A Systematic Scoping Review of Current Literature and Identified Knowledge Gaps - Yumiko Coffey; Navjot Bhullar; Joanne Durkin; Md Shahidul Islam; Kim Usher (Elsevier, 2021)
Eco-anxiety is the distress caused by climate change where people are becoming anxious about their future. The present scoping reveiw critically evaluated and synthesized the scholarly literature on eco-anxiety and reported it using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for scoping reviews (PRISMA-ScR) [1]. The study aims were twofold: (i) to understand how eco-anxiety was operationalized in the existing literature, and (ii) the key characteristics of eco-anxiety. Our review found that further research is needed to provide conceptual clarity of the term eco-anxiety. We found that most of the evidence comes from the Western countries, and future research is needed in the non-Western countries. Indigenous peoples, children and young people, and those connected to the natural world are most impacted by eco-anxiety and are identified as vulnerable. We recommend employing diverse methodologies to better understand their lived experiences of eco-anxiety.